2008
DOI: 10.3748/wjg.14.4805
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for local recurrence of middle and lower rectal carcinoma after curative resection

Abstract: AIM:To explore the risk factors for local recurrence of middle and lower rectal carcinoma after curative resection. METHODS: Specimens of middle and lower rectal carcinoma from 56 patients who received curative resection at the Department of General Surgery of Guangdong Provincial People's Hospital were studied. A large slice technique was used to detect mesorectal metastasis and evaluate circumferential resection margin status. The relations between clinicopathologic c h a r a c t e r i s t i c s , m e s o r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Wu et al (24) studied 56 patients who were surgically treated for middle and lower rectal carcinoma and found 7 (12.5%) cases with local recurrence. They reported that high preoperative CEA levels and neoplasic venous emboli were significantly correlated with recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (24) studied 56 patients who were surgically treated for middle and lower rectal carcinoma and found 7 (12.5%) cases with local recurrence. They reported that high preoperative CEA levels and neoplasic venous emboli were significantly correlated with recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Following resection, circumferential margin positivity and tumor perforation are the primary factors that influence the development of locoregional recurrence (19).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study with 1,146 patients with CRC found that, following use of a multivariate analysis, preoperative CEA levels proved a highly significant prognostic factor even when stage and grade were introduced in the model ( 150 ). In addition, elevated preoperative CEA in stage III and IV CRC are considered to be a potent independent risk factor as far as local relapse, short disease-free survival and OS are concerned ( 151 ).…”
Section: Prognostic Markersmentioning
confidence: 99%